Physical Fitness of Thoroughbred Horse Racing Jockeys - Kylie A. Legg; Darryl J. Cochrane; Erica K. Gee; Yin Y. Chin; Chris W. Rogers (Journal of Science in Sport and Exercise, 2025)
Purpose Thoroughbred racing jockeys compete at maximum physiological capacity in a sport with a high risk of falls and injury. A greater understanding of the physical capacities determining jockey performance may lead to minimum physical performance parameters and corrective interventions to improve jockey fitness and performance and reduce jockey and horse injury. The aim of this study was to develop appropriate physical testing procedures for jockeys and a physical fitness profile for different licence levels. Methods Fifty-eight jockeys ( n = 24 females, n = 34 males), representing all apprentice jockeys licenced in New Zealand in 2021 (100%, n = 8 probationers and n = 39 apprentices) and eleven professional jockeys (14%) were assessed to determine baseline physiological and fitness data. Descriptive statistics and boxplots were used to compare aerobic fitness, abdominal (core), upper and lower body strength, muscular power, reaction time, flexibility and a novel ‘saddle’ test targeting lower body strength, balance, and endurance between licencing levels. Effect Size (ES) was used to determine magnitude of differences between groups. Results More experienced jockeys had greater relative lower body strength (ES = 0.2–0.7) and better balance (ES = 0.5–0.9) compared to the less experienced groups. Jockeys who were in the top 20 of the premiership table (jockey rankings) had faster reaction times (ES = 0.7) and greater core extensor strength (ES = 0.7) than other cohorts. Most tests showed little differentiation between jockey licence levels, however the ‘saddle test’ showed greater variability in the less experienced race riders. This test may be an effective measure of jockey baseline performance. Conclusions These data could be used to inform minimum jockey licencing requirements and future physical fitness training programmes to increase jockey physiological fitness, thereby minimising risk of falls or injury due to physiological deficits and performance.

Classification of direct threats to the conservation of ecosystems and species 4.0 - Nick Salafsky; Claire Relton; Bruce E. Young; Philippe Lamarre; Monika Böhm; Maxime Chénier; Erica Cochrane; Mark Dionne; Kevin K. He; Craig Hilton‐Taylor; Charles Latrémouille; John Morrison; et al. (Conservation Biology, 2025)
Identifying and assessing the magnitude of direct threats to ecosystems and species are critical steps to prioritizing, planning, implementing, and assessing conservation actions. Just as medical clinicians and researchers need a standard way to talk about human diseases, conservation practitioners and scientists need a common and comprehensive language to talk about the threats they are facing to facilitate joint action, evaluation, and learning. To meet this need, in 2008 the IUCN Species Survival Commission and the Conservation Measures Partnership produced the first version of a common threats classification with the understanding that it would be periodically updated to take into account new information and learning. We present version 4.0 of this classification. For this latest update, we reviewed existing versions and derivatives of the original classification, over 1000 citations of the classification, threats data from over 2900 real‐world conservation projects, and comments from many users. Based on our findings, we made changes to the threats classification scheme, including addition of a level 0 threat class, refinement of levels 1 and 2 threat categories, and addition of the threat “Fencing & walls” to level 2. Also added were level 3 threat types and modifiers that provide a more detailed description of different types of direct threats and thus allow users to fine‐tune analyses and actions. The update also clarifies how to treat various stressors, including natural disaster events and climate change. As a result of these changes, we revised the formal definition of direct threats. They include human actions that are the direct cause of ecosystem or species‐population degradation and loss, such as agriculture, transport, natural resource use, and ecosystem management. They also include ultimate stressors in natural systems whose dynamics have been altered by the effects of current or historical human actions, such as invasive or problematic native species, pollution, natural disasters, and climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)